Analysis of Optical Properties of Graphene Oxide from Bamboo Petung (Dendrocalamus Asper) Synthesized by Modified Hummer Method - Indah Safira; Ramli; Yenni Darvina; Fadhila Ulfa Jhora (Journal of Experimental and Applied Physics, 2023)
Carbon, hydrogen and oxygen are abundant in the structure of graphene oxide (GO), often known as graphene. In this study, petung bamboo was used in the manufacture of graphene oxide. The aim of this research is to find out how the sintering temperature influences the ability of graphene oxide to absorb waves. The modified hummer method is used to oxidize graphite and produce Graphene Oxide. This research was divided into several parts, namely burning carbonized petung bamboo, production of graphene oxide, and sonication and neutralization of graphene oxide using sintering temperatures of 300°C, 350°C, 400°C and 450°C. The synthesis results were characterized using a UV-Vis spectrometer to obtain an absorption spectrum resulting in a band gap of 2.68 eV-4.38 eV in Petung bamboo at a sintering temperature of 300oC - 400oC, the bandgap increasing as the sintering temperature increased. At a sintering temperature of 400oC - 450oC the band gap value decreases which is influenced by the results of cell changes from refinement which can change the band structure thereby affecting the size of the band gap. The absorption value obtained in the optical properties decreases because the high sintering temperature causes the reaction rate to become faster so that the absorption value becomes lower.